Penerapan Metode Demonstrasi Pada Pembelajaran Menulis Teks Eksplanasi Peserta Didik Kelas VIII SMPN 31 Semarang Tahun Ajaran 2023/ 2024 - Rizal Muhaimin; Arisul Ulumuddin; Suyoto Suyoto (CV. Alim's Publishing, 2023)
This research is motivated to show the lack of enthusiasm of students in learning activities, especially Indonesian learning. Learning activities Indonesian, students lack focus so that it causes boredom during learning. So a special method is needed to foster the enthusiasm of students so that the learning process can take place well. The demonstration method is a teaching method by demonstrating goods, events, rules, and sequences in carrying out activities, directly and using teaching media that are relevant to the subject matter or material that has been presented. Based on this background, the problem arises how to apply the demonstration method in learning to write explanatory texts for grade VIII students of SMPN 31 Semarang for the 2023/2024 school year? This study aims to identify the application of demonstration methods in learning to write explanatory texts.